Les symboles bibliques dans la publicité : développement, contextes, conflits - Jérôme Cottin (Communiquer)
For about three decades, advertisement has been using, implicitly or explicitly, biblical and Christian quotes. It diverts them or turn them into metaphors in playful, evocative, or humoristic ways. This study will analyze a certain number of examples, from France and Germany essentially, and will focus on their contextualization and their reception. It will present a few advertisements that have been the object of contestation, sometimes virulent, in France. It will show the recent evolution of this phenomenon, which sees these religious allusions evolve towards the evocation of an orientalizing spirituality, privileging wellbeing, and the personal aspiration to happiness.